2016
DOI: 10.1039/c5cp04549e
|View full text |Cite
|
Sign up to set email alerts
|

Conformational ensemble of human α-synuclein physiological form predicted by molecular simulations

Abstract: We perform here enhanced sampling simulations of N-terminally acetylated human α-synuclein, an intrinsically disordered protein involved in Parkinson's disease. The calculations, consistent with experiments, suggest that the post-translational modification leads to the formation of a transient amphipathic α-helix. The latter, absent in the non-physiological form, alters protein dynamics at the N-terminal and intramolecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 52 publications
7
35
0
Order By: Relevance
“…[32,42] Quantitative agreement in the relative amounts, instead, is more difficult to test because accurate simulations of disordered conformational ensembles are highly challenging. [43][44][45] Nevertheless, comparison with experimental solution methods has shown good agreement with species distributions obtained by native-MS for unfolding transitions of globular proteins. [41,46] The role of SASA during protein electrospray can be rationalized by the results of computational simulations of protein structures under electrospray conditions.…”
Section: Doi: 101002/pmic201800060mentioning
confidence: 77%
“…[32,42] Quantitative agreement in the relative amounts, instead, is more difficult to test because accurate simulations of disordered conformational ensembles are highly challenging. [43][44][45] Nevertheless, comparison with experimental solution methods has shown good agreement with species distributions obtained by native-MS for unfolding transitions of globular proteins. [41,46] The role of SASA during protein electrospray can be rationalized by the results of computational simulations of protein structures under electrospray conditions.…”
Section: Doi: 101002/pmic201800060mentioning
confidence: 77%
“…Because the histidine 50 (H50) residue is key for anchoring Cu 2+ binding to aSyn, the results suggested that the critical step for the effects observed in Cu 2+ -mediated aSyn aggregation might be the formation aSyn-Cu 2+ complexes at this site. In vitro NMR (28) and electron paramagnetic resonance (26,29) experiments have suggested that the ion binds in a square planar or tetrahedral distorted geometry, involving 2 or 3 N ligands and 2 or 1 O ligands, respectively (29)(30)(31). Models A and B (SI Appendix, SI Molecular Simulations) have been proposed in the literature (28,29,32).…”
Section: Resultsmentioning
confidence: 99%
“…Although the CD spectroscopy showed a characteristic negative peak at ~ 218 nm for both acetylated-S and WT-S fibrils, the acetylated-S fibrils had slightly higher β sheet content (Figure 5.5C). Similar differences in calculated CD spectra have been recently reported for S with and without N-terminal acetylation by MD simulations 268 . The mean fibril length of WT-S was ~ 6 fold higher than the acetylated-S fibril length (Figure 5.6).…”
Section: Resultssupporting
confidence: 88%